Routine germline BRCA1 and BRCA2 testing in patients with ovarian carcinoma: analysis of the Scottish real‐life experience. (10th May 2018) - Rust, K; Spiliopoulou, P; Tang, CY; Bell, C; Stirling, D; Phang, THF; Davidson, R; Mackean, M; Nussey, F; Glasspool, RM; Reed, NS; Sadozye, A; et al.
Abstract : Objective: To determine the rates of germline BRCA1 and BRCA2 mutations in Scottish patients with ovarian cancer, before and after a change in testing policy. Design: Retrospective cohort study. Setting: Four cancer/genetics centres in Scotland. Population: Patients with ovarian cancer undergoing germline BRCA1 and BRCA2 ( gBRCA1/2 ) sequencing before 2013 (under the 'old criteria', with selection based solely on family history), after 2013 (under the 'new criteria', with sequencing offered to newly presenting patients with non‐mucinous ovarian cancer), and in the 'prevalent population' (who presented before 2013, but were not eligible for sequencing under the old criteria but were sequenced under the new criteria). Methods: Clinicopathological and sequence data were collected before and for 18 months after this change in selection criteria. Main outcome measures: Frequency of germline BRCA1, BRCA2, RAD51C, and RAD51D mutations. Results: Of 599 patients sequenced, 205, 236, and 158 were in the 'old criteria', 'new criteria', and 'prevalent' populations, respectively. The frequency of gBRCA1/2 mutations was 30.7, 13.1, and 12.7%, respectively. The annual rate of gBRCA1/2 mutation detection was 4.2 before and 20.7 after the policy change. A total of 48% (15/31) 'new criteria' patients with gBRCA1/2 mutations had a Manchester score of <15 and would not have been offered sequencing based on family history criteria. In addition, 20 patients with gBRCA1/2 were identified in the prevalent population. The prevalence of gBRCA1/2 mutations in patients aged >70 years was 8.2%. Conclusions: Sequencing all patients with non‐mucinous ovarian cancer gives a much higher annual gBRCA1/2 mutation detection rate, with the frequency of positive tests still exceeding the 10% threshold upon which many family history‐based models operate. Tweetable abstract: BRCA sequencing all non‐mucinous cancer patients increases mutation detection five fold. Tweetable abstract: BRCA sequencing all non‐mucinous cancer patients increases mutation detection five fold.